THE EFFECT OF COLLABORATIVE WRITING ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMP KARTIKA 1-5 PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Eka Ernawati; Eliwarti Eliwarti; Afrianto Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The objective of this research was to find out whether there is a significant effect of collaborative writing on the students’ ability of SMP Kartika 1-5 Pekanbaru in writing descriptive texts. The design of this research was pre-experimental research with one group pre-test post-test design. A single group was selected to be a sample by using cluster random sampling. There were 28 students as the sample. The instrument was writing tests used both in pre-test and post-test. Then, the data were analyzed by using t-test formula. After the data were analyzed, it was found that t-test score was 9.785 while t-table score in significance level 5% df= 27 was 2.051. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted. It means that “there is a significant effect of collaborative writing on the students’ ability of SMP Kartika 1-5 Pekanbaru in witing descriptive texts”. Based on the research findings, it is suggested that collaborative writing can help the students improve their writing ability especially in writing descriptive texts.Key Words: Effect, Collaborative Writing, Writing Ability, Descriptive Text